Effectiveness of Balance Exercises on Postural Control and Quality of Life in Patients with Lumbar Discopathy - KURU ÇOLAK, TUĞBA (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: Lumbar discopathy is a common problem that affects musculoskeletal system. Many treatment modalities are in use for patients with lumbar discopathy. Balance exercises could be important for the lumbar discopathy due to the affected musculoskeletal system. This study was planned to investigate the effect of balance exercises on postural control and quality of life for lumbar discopathy. Method: A total of 81 patients were divided into two as the intervention and the control groups. Therapeutic ultrasound, transcutaneous electrical nerve stimulation (TENS), hotpack and therapeutic exercises were applied to all patients 5 times a week during thirty sessions. Additionally, the intervention group received balance exercises. Pain (Visual Analog Scale), disability (Oswestry Disability Index), quality of life (Short Form-36) and postural control (Libra (R)) have been evaluated by same physiotherapist before and after the treatment. Results: Statistically significant differences were found between the groups comparing pain, disability and postural control parameters (p<0.05). In the between group comparisons of the mean changes of the 'Quality of Life' assessment parameters, no significant differences were obtained between the intervention and control groups (p>0.05), except the 'physical role' parameter in favor of the control group (p=0.04). Conclusion: This study demonstrated that physiotherapy modalities improve pain, disabiliy, quality of life and postural control parameters in patients with lumbar discopathy but adding classic balance exercises in physiotherapy treatment, do not have a remarkable effect in patients with lumbar discopathy.
Keywords: Lumbar discopathy; balance exercises; postural control; quality of life; physiotherapy